Implementing efficient and sustainable collaboration between National Immunization Technical Advisory Groups: Report on the 3rd International Technical Meeting, Paris, France, 8–9 December 2014. Issue 11 (8th March 2016) - Perronne, Christian; Adjagba, Alex; Duclos, Philippe; Floret, Daniel; Houweling, Hans; Le Goaster, Corinne; Lévy-Brühl, Daniel; Meyer, François; Senouci, Kamel; Wichmann, Ole
Abstract: Many experts on vaccination are convinced that efforts should be made to encourage increased collaboration between National Immunization Technical Advisory Groups on immunization (NITAGs) worldwide. International meetings were held in Berlin, Germany, in 2010 and 2011, to discuss improvement of the methodologies for the development of evidence-based vaccination recommendations, recognizing the need for collaboration and/or sharing of resources in this effort. A third meeting was held in Paris, France, in December 2014, to consider the design of specific practical activities and an organizational structure to enable effective and sustained collaboration. The following conclusions were reached: (i) The proposed collaboration needs a core functional structure and the establishment or strengthening of an international network of NITAGs. (ii) Priority subjects for collaborative work are background information for recommendations, systematic reviews, mathematical models, health economic evaluations and establishment of common frameworks and methodologies for reviewing and grading the evidence. (iii) The programme of collaborative work should begin with participation of a limited number of NITAGs which already have a high level of expertise. The amount of joint work could be increased progressively through practical activities and pragmatic examples. Due to similar priorities and already existing structures, this should be organized at regional or subregional level. For example, in the European Union a project is funded by the European Centre for Disease Prevention and Control (ECDC) with the aim to set up a network for improving data, methodology and resource sharing and thereby supporting NITAGs. Such regional networking activities should be carried out in collaboration with the World Health Organization (WHO). (iv) A global steering committee should be set up to promote international exchange between regional networks and to increase the involvement of less experienced NITAGs. NITAGs already collaborate at the global level via the NITAG Resource Centre, a web-based platform developed by the Health Policy and Institutional Development Unit (WHO Collaborating Centre) of the Agence de Médecine Préventive (AMP-HPID). It would be appropriate to continue facilitating the coordination of this global network through the AMP-HPID NITAG Resource Centre. (v) While sharing work products and experiences, each NITAG would retain responsibility for its own decision-making and country-specific recommendations.